MC The Newsletter of Masscomm 2025 (Volume 3) - Khamis, Muhamad Hanapi; Abu Bakar, Muhammad Nabihan; Ismail, Siti Nasarah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Welcome to Volume 3 of the Faculty of Communication and Media Studies, UiTM Rembau E-Buletin. This edition highlights the dynamic role of Artificial Intelligence (AI) in Creative Communication which focusing on creative strategies, visual design, narrative construction, media tools, and content creation. The contributions presented reflect both scholarly depth and creative innovation, showcasing the intellectual vitality of our community. This publication not only informs and inspires but also fosters critical dialogue on the evolving intersections of communication and technology. Heartfelt appreciation is extended to all contributors for their dedication and we sincerely thank all include readers for your continued support. Happy and insightful reading!